2021
DOI: 10.1063/5.0046225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-plane shear flow on the magnetic island coalescence instability

Abstract: Using a 2D Viscoresistive Reduced MagnetoHydroDynamic model, the magnetic island coalescence problem is studied in the presence of in-plane, parallel shear flows. Extending the analytical work of Waelbroeck et al. [Phys. Plasmas 14, 022302 (2007)] and Throumoulopoulos et al., [J. Phys. A 42, 335501 (2009)] in the sub-Alfvénic flow shear regime for Fadeev equilibrium, the super-Alfvénic regime is studied for the first time numerically. A wide range of values of shear flow amplitudes and shear scale lengths have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, the focus has been predominantly on plasma energization. In the nonrelativistic regime, the shear flow effects on reconnection dynamics are more well studied (La Haye et al 2010;Nakamura et al 2013;Mahapatra et al 2021;Paul & Vaidya 2021). It has been shown that shear flows have a stabilizing effect on the tearing instability and can decrease the reconnection rate in the nonlinear stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus has been predominantly on plasma energization. In the nonrelativistic regime, the shear flow effects on reconnection dynamics are more well studied (La Haye et al 2010;Nakamura et al 2013;Mahapatra et al 2021;Paul & Vaidya 2021). It has been shown that shear flows have a stabilizing effect on the tearing instability and can decrease the reconnection rate in the nonlinear stage.…”
Section: Introductionmentioning
confidence: 99%